Genetic Risk Factors for Endometriosis. Issue 2 (2017) - Fung, Jenny N.; Sapkota, Yadav; Nyholt, Dale R.; Montgomery, Grant W.
Advances in genetics and genomics are driving progress in understanding genetic risk factors for endometriosis. Genome-wide association scans (GWAS) in endometriosis have identified 11 genomic regions associated with increased risk of disease. Many of the regions contain interesting candidate genes, but the risk alleles may not always act through the obvious candidates. Functional evidence to identify the causal gene(s) will require multiple steps including better mapping precision, genetic studies on gene expression and epigenetic marks, chromatin looping and functional studies. Evidence from gene expression studies in endometrium and chromatin looping experiments implicate CDC42 on chromosome 1, CDKN2B-AS1 on chromosome 9 and VEZT on chromosome 12 as likely causal genes in these regions. Confirming the causal gene(s) in these and other regions will identify the important pathways increasing risk for endometriosis and identify novel targets for interventions to improve diagnosis and treatment.